Epidemiology of falls in 25 Australian residential aged care facilities: a retrospective longitudinal cohort study using routinely collected data. (19th May 2022) - Wabe, Nasir; Seaman, Karla L; Nguyen, Amy D; Siette, Joyce; Raban, Magdalena Z; Hibbert, Peter; Close, Jacqueline C T; Lord, Stephen R; Westbrook, Johanna I
Abstract: Background: Falls are frequent among older adults and have significant health and economic consequences. There have been few studies on the epidemiology of falls in residential aged care facilities (RACFs). Objective: To determine the incidence of falls in RACFs using longitudinal routinely collected incident data over 5 years (July 2014–December 2019). Methods: A retrospective cohort study is conducted using fall incident data from 25 RACFs in Sydney, NSW, Australia. Incidents relating to a population of 6163 aged care residents aged ≥65 years were included. Outcome measures were incidents of all falls, injurious falls and falls requiring hospitalization. The risk-adjusted incidence rate (IR) for each outcome indicator for each of the 25 facilities was calculated. Results: A total of 27 878 falls were reported over 3 906 772 resident days (a crude rate of 7.14 incidents per 1000 resident days; 95% confidence interval (CI) 6.81–7.48). Of these, 10 365 (37.2%) were injurious and 2733 (9.8%) required hospitalization. The crude IRs were 2.65 incidents per 1000 resident days (95% CI 2.53–2.78) for injurious falls and 0.70 incidents per 1000 resident days (95% CI 0.66–0.74) for falls requiring hospitalization. The incidence of falls was significantly higher in respite compared to permanent residents for all falls (adjusted IR ratio (aIRR) 1.33; 95% CI 1.18–1.51) and injurious falls (aIRR 1.30; 95% CI 1.14–1.48) and for men compared to women for all outcomes (all falls aIRR 1.69; 95% CI 1.54–1.86; injurious falls aIRR 1.87; 95% CI 1.71–2.04 and falls requiring hospitalization aIRR 1.29; 95% CI 1.12–1.48). The risk-adjusted IRs per 1000 resident days between facilities varied substantially (all falls 0.57–12.93 falls; injurious falls 0.25–4.47 and falls requiring hospitalization 0.10–1.70). Conclusion: Falls are frequent in RACFs, often resulting in injury and hospitalization. The study provides robust and comprehensive information that may help inform future initiatives to minimize the incidence of falls in RACFs.